Computer Science
Reduce the following to its simplest form using laws of boolean algebra. At each step clearly state the law used for simplification.
A.B' + A'.B.C' + (A.C') + B.C
Answer
A.B' + A'.B.C' + (A.C') + B.C
= A.B' + A'.B.C' + (A.C')(B+B') + B.C [Complementary Law: B+B'=1]
= A.B' + A'.B.C' + A.B.C' + A.B'.C' + B.C [Distributive Law]
= A.B' + A.B'.C' + A'.B.C' + A.B.C' + B.C [Associative Law]
= A.B' + A'.B.C' + A.B.C' + B.C [Absorbtion Law: A.B' + A.B'.C' = A.B']
= A.B' + B.C + B.C'(A' + A)
= A.B' + B.C + B.C'.1 [Complementary Law: A+A'=1]
= A.B' + B(C + C')
= A.B' + B [Complementary Law: C+C'=1]
= (A + B).(B' + B) [Distributive Law]
= A + B [Complementary Law: B+B'=1]
Related Questions
Simplify a.b + a'.c + b.c using the laws of boolean algebra. At each step, state clearly the law used for simplification.
What is the application of boolean algebra in computer science?
State the dual form of the following boolean expression:
X.Y'(X.Y'.Z + X + X'.Z')Explain the following:
- Canonical sum of product
- Canonical product of sum